A Compound Odontoma: Case Report and Review - M. PAVANI MDS; Y.V. HEPHZIBAH BDS (International Journal of Pharma and Bio Sciences, 2018)
Odontomas are the most common type of odontogenic tumors which is benign, slow growing, nonaggressive, asymptomatic and usually associated with the impacted or delayed eruption of the permanent teeth. Odontoma is a tumor of unknown etiology and is frequently found associated with a dental germ in development, a supernumerary tooth, or even a primary tooth retained in the arch. Here, we present a case report of a compound odontoma in 25years old male which resulted in failure of eruption of the permanent maxillary left canine while the contralateral tooth has erupted. The aim of this study was to present review on etiology, clinical presentational and radiographical features of the compound odontoma a rare case. Result obtained is Compound odontoma occur often in the anterior region of the jaws. The most common clinical manifestations were the impacted permanent teeth. To be conclude the earlier the diagnosis and treatment greater would be the prognosis which in turn avoid esthetics problem, developmental disturbance of dentition, occlusion and craniofacial complication.